Analysis of Social Return on Investment (SROI) on the Utilization of Mauquf 'Alaih Funds for Micro, Small and Medium Enterprises - Abdussalam, Abdussalam; Gunawan, Aditya Rahmat (JURNAL EKONOMI SYARIAH, 2024)
Introduction to The Problem: Most Indonesians understand that waqf only applies to certain assets that are not growing, nowadays waqf management must begin to shift in a more productive direction so that it can provide wider benefits. The concept of productive waqf is a new paradigm in developing waqf assets where the proceeds from these assets can empower the community.Purpose/Objective Study: This research aims to measure the impact of utilizing mauquf 'alaih funds managed by Rumah Wakaf to help business actors, micro, small and medium (MSMEs) in the process of their business activities so that they become better and can increase income..Design/Methodology/Approach: This research uses Social Return on Investment (SROI) analysis, the method used is a mix method by combining qualitative and quantitative. The sample was determined using purposive sampling and data collection through field observations, in-depth interviews and document studies, while determining the SROI ratio value using the equation of Net Present Value of Benefit and Net Present Value of Investment.Findings: The findings of this research show that the impact of utilizing mauquf 'alaih funds provided in the form of business carts based on SROI calculations is 1.95 : 1, meaning that every Rp 1 contribution will produce a benefit of Rp 1.95. So that the mauquf 'alaih funds generated from productive waqf have an impact on business actors and can be categorized as a feasible and targeted program.Paper Type: Research Article.